Checking Executive Personalism: Collegial Governments and the Level of Democracy*. Issue 3 (20th August 2020) - Altman, David
Abstract: The world is facing a tide of "cult‐of‐personality" governments that threaten liberal democracy (e.g., Trump, Duterte, Bolsonaro, Orbán). Collegial executives are a long‐established institutional alternative, predicated upon disarming this very shortcoming in the practice of democracy. These are regimes in which multiple people share power, limiting executive excess. Historiographic accounts regard the collegial executive as inimical to resolute decision‐making and responsible for democratic deterioration. Despite being used since antiquity, there is no empirical research on how collegial executives influence democracy. This paper tests, for the first time, whether collegial executives are substantially worse for democracy than single‐leader executives. The focus is on the only robust polyarchy to have alternated twice between single‐person and collegial‐executive governments: Uruguay. Using the Synthetic Control Method, the paper creates a fictional Uruguay to compare with the country's real experience. The results show that multiple‐executive governments have had no impact on Uruguay's level of democracy.